Karta Rogawskiego. Zapomniany zabytek języka staropolskiego - Rojszczak-Robińska, Dorota (Slavia Occidentalis, 2017)
The article is a new edition of Karta Rogawskiego, a forgotten 15th century work written in the Polish language. The previous edition, available only in transliteration, comes from 1911. It is a single parchment sheet torn from a different code and then used as a cover, now partly illegible. The content revolves around a scene of Jesus being interrogated by Pontius Pilate, who delivers judgement. The article provides a new transliteration as well as transcription; photographs of the the manuscript have also been attached.